Facile self-assembly synthesis of γ-Fe2O3 /graphene oxide for enhanced photo-Fenton reaction. (May 2019) - Wang, Feifei; Yu, Xiaolin; Ge, Maofa; Wu, Sujun; Guan, Juan; Tang, Junwang; Wu, Xiao; Ritchie, Robert O.
Abstract: A novel self-assembly method was developed to prepare a γ-Fe2 O3 /graphene oxide (GO) heterogeneous catalyst that showed excellent synergy between photocatalysis and Fenton-like reactions. The γ-Fe2 O3 /GO catalyst prepared on the iron plates demonstrated efficient and reproducible catalytic activities for water treatment. It takes only 80 min to degrade 50 mg L −1 methylene (MB) completely, which is the main non-biodegradable dye in wastewater from the textile industry. The heterogeneous catalyst is stable over a wide range of pH (from 2.0 to 10.2) for MB degradation, and can be easily extracted from solution and repeatedly used with little loss of catalytic activity. The high activity and stability of the catalyst system can be attributed to charge separation between γ-Fe2 O3 and GO, which could accelerate Fenton-like process and photocatalysis. In addition, the dominant reactive oxidant species responsible for the MB degradation, including the hydroxyl radicals (OH) and holes (h + ), were trapped on the surface of the γ-Fe2 O3 /GO composite, as proved by a free-radical quenching experiment. The γ-Fe2 O3 /GO heterogeneous catalyst could potentially provide a solution for removal of non-biodegradable dyes from wastewater in the textile industry. Graphical abstract: Schematic illustration of the proposed mechanism for MB degradation of γ-Fe2 O3 /GO catalyst under UV irradiation. Image 1 Highlights: The γ-Fe2 O3 /GO composite were prepared by a self-assembly method which is much easier and more efficient than other methods. The γ-Fe2 O3 /GO composite demonstrated great catalytic activity. The synergistic interaction between γ-Fe2 O3 and GO was in-depth discussed.